PENGEMBANGAN MEDIA PEMBELAJARAN GOOGLE SITES PADA MATERI HIDROLISIS GARAM BERBASIS PENDEKATAN KONTEKSTUAL - Dewi Ratna Sari; Retno Aliyatul Fikroh; Riawati Rahayu; Pandu Ridzaniyanto (UIN AR-RANIRY, 2022)
Google sites can be used as an alternative interactive chemistry learning media, especially on salt hydrolysis material. This research aims to develop learning media in the form of google sites based on a contextual approach to salt hydrolysis material and to test the quality of the developed media. The research carried out is in the form of development research using a 4-D research model (define, design, develop, and disseminate), but is only limited to the develop. Assessment of product quality is carried out using a Likert obtained from the validator and student responses using a Guttman. The results of the assessment of product quality by material experts obtained a percentage of 88.63% in the Very Good category (VG), the assessment by media experts obtained a percentage of 92.5% in the Very Good category (VG), and the assessment by reviewers obtained a percentage of 90.47% in the form of the Very Good (VG) category and positive responses by students who obtained a percentage of 94% in the Very Good (VG) category. Based on the assessments of media experts, material experts, reviewers, and student responses, it can be concluded that the developed media can be used as an alternative medium for chemistry learning on salt hydrolysis material.